Challenges in the pharmacological treatment of geriatric asthma. Issue 7 (2nd July 2016) - Agusta, Fabio; Battaglia, Salvatore; Benfante, Alida; Spatafora, Mario; Scichilone, Nicola
ABSTRACT: Asthma in older populations is characterized by frequent comorbid conditions, which increase the risk of side effects and of detrimental interactions between respiratory and non-respiratory drugs. These observations lead to the need to manage asthma in older populations by applying a multidimensional assessment and a multidisciplinary treatment; therefore, we favor the use of the 'geriatric' term to define asthma in the elderly. Geriatric asthma is a complex disease, which may not necessarily imply that it is also complicated, although the two conditions may often coexist. On this basis, the switch from an organ-driven management to the holistic approach may be the key factor to attain optimal control of the disease in this age range. The current review discusses the age-related factors affecting asthma treatment in the oldest individuals, such as the comorbid conditions, and age-related changes of metabolism and excretion that can impair the efficacy and safety of drugs.